ANALISIS TATA KELOLA RUANG TERBUKA HIJAU KABUPATEN KARAWANG - Uu Idjudin Solihin; Mitari Dianrachma; Arief Darmawan Tobing (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
The existence of Green Open Space is regulated in Act Number 26 of 2007 concerning Spatial Planning which was then followed up by the Karawang Regional Government by making the Karawang Regency Regulation Number 2 of 2015 concerning Management of the Green Open Space of Karawang Regency. How far the arrangement of Green Open Space is accommodated in Karawang District Regulation Number 2 of 2015 concerning Management of Karawang Regency Green Open Space. The research method uses normative juridical analysis through the suppression of legislation, library materials, and other secondary data. The results of this study confirm that the Karawang District Regulation Number 2 of 2015 concerning Management of Green Open Spaces in Karawang Regency is sufficient to accommodate regulations related to Green Open Spaces in particular.